RANCANG BANGUN MESIN SPINNER UNTUK MEMBANTU PROSES PENIRISAN MINYAK KERIPIK GADUNG DI UMKM PAWON D’TIENS - Rizky Pratama; Dian Setiya Widodo (AGROTERAP : Prodi Agroindustri Universitas 17 Agustus 1945 Surabaya, 2023)
Pawon D'tiens UMKM, located in Begaganlimo Village, Gondang District, Mojokerto Regency, East Java, manufactures gadung chips from gadung tubers that have been processed through many stages. The problems in Pawon D'tiens UMKM that will be resolved by this research are specifically in the oil draining process, where the draining process is still manual, and there is still a lot of oil stuck to the gadung chips, which can reduce the quality of the chips, for example, the chips crumble easily, have a rancid smell, and don't last long, making consumers less interested. As a result, we wish to assist Pawon D'tiens MSMEs in problem resolution by building machinespinners as needed and adding a rotating speed controller. This study focuses on the design of a transmission system that incorporates shafts, a pulley, and a v-belt.In designing the transmission system, the research acquired the following results: axles built of 20 mm ST 40 iron, pulleys measuring 100 mm and 200 mm, and v-belt type B-68 with a circumferential length of 1727.2 mm.